Legal Aid for Communities Affected by Covid-19 - Nisak, Iva Latifatun (The Indonesian Journal of International Clinical Legal Education, 2020)
At present the world is in an uproar with the advent of a coronavirus. This virus first appeared in Wuhan, China in 2019. On December 31, 2019, Chinese authorities notified the World Health Organization (WHO) of a new corona virus outbreak that caused severe illness. The virus has now spread to all continents, except the Antarctic continent. Until Wednesday, March 18, 2020, there were 201,530 positive cases of the Corona Virus, 8,007 patients died, and 82,034 others recovered. The case is widespread because transmission can occur between humans. One of the countries affected by the corona virus outbreak is Indonesia. In Indonesia it is called the Covid-19 pandemic. With the spread of this virus to Indonesia, it has had several impacts for the Indonesian people themselves. This virus carries ampak which is very dangerous for health, coronavirus attacks the respiratory system. The impact of this virus infection is mild to severe even to cause death in sufferers. The co-19 pandemic outbreak in Indonesia, based on data from the Ministry of Health, recorded a total of positive people affected by the corona virus as of 31 March 2020 reaching 1,528 people, 81 of whom were declared cured, and 136 were declared dead.